Corticosteroid tapering with benralizumab treatment for eosinophilic asthma: PONENTE Trial - Andrew Menzies-Gow; Jonathan Corren; Elisabeth H. Bel; Jorge Maspero; Liam G. Heaney; Mark Gurnell; Peter Wessman; Ubaldo J. Martin; Shahid Siddiqui; Esther Garcia Gil (ERJ Open Research, 2019)
Benralizumab is an interleukin-5 receptor α-directed cytolytic monoclonal antibody approved in several countries for the add-on maintenance treatment of patients with severe eosinophilic asthma aged 12 years and older. In the 28-week Phase III ZONDA trial (ClinicalTrials.gov identifier: NCT02075255), benralizumab produced a median 75% reduction from baseline in oral corticosteroid (OCS) dosage (versus 25% for placebo) while maintaining asthma control for patients with OCS-dependent severe asthma. This manuscript presents the detailed protocol for the Phase IIIb PONENTE (ClinicalTrials.gov identifier: NCT03557307), a study that will build on the findings from ZONDA. As the largest steroid-sparing study undertaken in severe asthma, PONENTE has a faster steroid tapering schedule for prednisone dosages ≥7.5 mg·day−1 than previous studies, and it includes an evaluation of adrenal insufficiency and an algorithm to taper OCS dosage when prednisone dosage is ≤5 mg·day−1. It also has a longer maintenance phase to assess asthma control for up to 6 months after completion of OCS tapering. The two primary endpoints are whether patients achieve 100% reduction in daily OCS use and whether patients achieve 100% reduction in daily OCS or achieve OCS dosage ≤5 mg·day−1, if adrenal insufficiency prevented further reduction, both sustained over ≥4 weeks without worsening of asthma. Safety and change from baseline in health-related quality of life will also be assessed. PONENTE should provide valuable guidance for clinicians on tapering OCS dosage, including the management of adrenal insufficiency, following benralizumab initiation for the treatment of patients who are OCS-dependent with severe, uncontrolled eosinophilic asthma.